The Influence of Work Discipline and Incentives on Employee Performance at PT YXZ Tex - Manoakh Nenobais; Nunung Ayu Sofiati; Gurawan Dayona Ismail; Yoyo Sudaryo; Ade Salman Alfarisi; Irving Ignatius Paul Luntungan; Riyandi Nur Sumawidjaya (Dinasti International Journal of Education Management And Social Science, 2025)
Performance is the result of work achieved by each employee that contributes positively to the company. This study aims to analyze the influence of work discipline and incentives on employee performance at PT XYZ Tex using structured modeling analysis (SEM) techniques. The descriptive study results from 120 employees who were the research sample indicate that Work Discipline, which includes compliance, attendance, and honesty, has been well established. Incentives, which include the process of providing incentives based on groups and the process of providing incentives based on individuals, have been implemented well by the company. Similarly, Employee Performance, which includes work quality, work quantity, task execution, and responsibility, has been well established. The results of the confirmatory study indicate a significant influence of the Work Discipline variable on Employee Performance with a partial influence of 11.5%. Furthermore, there is a significant influence of the Incentive variable on Employee Performance with a partial influence of 24.8%. Together, Work Discipline and Incentives have a significant influence on Employee Performance with a total influence of 60.2%. These findings highlight the importance of employees having work discipline and company strategies in providing incentives in order to improve employee performance.